A New Image Encryption Scheme Based on the Hybridization of Lorenz Chaotic Map and Fibonacci Q-Matrix - Hala I. Mohamed; Sarah M. Alhammad; Doaa Sami Khafaga; Osama El Komy; Khalid M. Hosny (IEEE Access, 2024)
In various image-processing applications, the fractional-order functions outperform their equivalent integer-order functions. In this study, we proposed a novel technique to encrypt color images with fractional-order chaotic systems, where the fractional-order simple Loranz is integrated with the FQM. Our novel part is hybridizing two maps (Lorenz & Fibonacci). The new algorithm benefits from the strengths of the fractional-order simple Lorenz chaotic system and the FQM to get a good performance technique. We confirm that our suggested encryption algorithms are effective and robust against attacks. Our suggested technique comprises numerous sequences: The primary color channels of the input image were separated into R-, G, and B-channel. The processes of confusion and diffusion are independent for each channel. The simple Loranz generates random integers using fractional ordering to enable pixel placements. We utilized the Fibonacci Q-matrix to dilute every $2^{*} 2$ block comprising the permitted image.